PENGKAJIAN STRATEGI KOMUNIKASI VISUAL PADA EVENT PINASTHIKA CREATIVE FESTIVAL AWARD TAHUN 2012 DAN 2013 - Hendi Ciputra (Saraswati)
In a creative event planning, it is required to be able to create something different than the others, in the process a promo event design needed to attract the target audience. To achieve that requires a creative strategy that can be packaged in a visual communication strategy for the design, in which a design is not only in great demand visual displays alone, but can combine the elements to be unified visual design that has a message in it to appeal to the see it. The research methodology used was a qualitative methodology, with a descriptive approach, where the data collected is the data in the form of literature studies, interviews and visual masterpiece in design promo event Pinasthika Creative Festival in 2012 and in 2013, the entire design in each event has the character and the messages in it. The results of this study indicate that each application design promo in every event contains the messages are packaged in a creative strategy visual unity that reflects the theme of the event in each year. There is something exciting breakthrough in managing an event that is periodic in nature, where in determining a theme for each year of its implementation, especially in 2012 and 2013, it still has a red thread so that the target audience are invited to always be able to tell you about its development, all of it presented and the designs represent the promo eventnya applications. The text has a very strong influence on other message elements in an attempt to explain the strategies presented. Each design promo event delivered as a communication strategy that represents the identity of the theme of the event. Keywords: AISAS (Attention, Interest, Search, Action, Share), application design promo event, Event Advertising, IMC (Integrated Marketing Communication).